Jews and Muslims under the Fourth Lateran Council: papers commemorating the octocentenary of the Fourth Lateran Council (1215) - Champagne, Marie Thèrèse; Resnick, Irven M. (Religion and law in medieval Christian and Muslim societies, 2018)
The Fourth Lateran Council (1215) was groundbreaking for having introduced to medieval Europe a series of canons that sought to regulate encounters between Christians and Jews and Muslims. Its canon 68 demanded that Jews and Muslims wear distinguishing dress, in order to prevent Christians from entering into illicit sexual relations with them, restricted the movement of Jews in public spaces during Holy Week, and exhorted secular authorities to punish Jews who in any way ?insult? or blaspheme against Christ himself. Other canons sought to exercise greater control over moneylending, to provide relief to Christian borrowers, to extract tithes from Jews who held Christian properties as pledges, and prohibited Jews from exercising power as public officials over Christians. The canons condemned converts who preserved elements from their former religion, promoted a fifth Crusade to the East, exempted Crusaders from taxes and from interest payments to Jewish moneylenders, restricted trade with Muslims or Saracens, and condemned Christians who provided arms or assistance to Saracens. The Council?s canons affected the missionary efforts of the late medieval Church and its attempts to convert Jewish and Muslim minorities, and established essential guidance on minority relations not to be surpassed until Vatican II in the 1960s